Third-Degree Atrioventricular Block And Asystole After Lung Resection: A Rare Complication - M. Castro, Patricia (2024)
Surgical resection remains the optimal therapeutic option for early-stage operable NSCLC. Despite significant advances in recent years related to anesthetic and surgical techniques, cardiopulmonary complications remain major causes for postoperative morbimortality.  In this paper we present a case of a patient who developed complete AV block followed by asystole after lung resection surgery. The patient underwent surgery via right VATS and the procedure was uneventful.  On the first post-operative day patient developed a third-degree atrioventricular block followed by 6 seconds asystole. Pharmacological treatment was instituted and implementation of a permanent pacemaker occurred on the third post-operative day, without complications. The remaining postoperative course was uneventful and the patient was discharged home on the sixth post-operative day.  It is the objective of the authors to report and highlight this rare and potencial fatal complication of lung resection.